Robust motion control of aerial manipulators. (2020) - Mimmo, N.; Macchelli, A.; Naldi, R.; Marconi, L.
Abstract: Aerial manipulators are composed of a robotic arm installed on an unmanned aerial vehicle and are used in several applications because of their inherent ability in performing complex tasks. In real-world applications, these systems are required to be robust against exogenous disturbances, such as wind, to guarantee the desired level of accuracy in the execution of the tasks. In this paper, the reference scenario consists of an aerial manipulator with a camera mounted on the end-effector of the robotic arm, and the goal is to track a fast-moving target. A control system architecture able to assure that the tracking error remains bounded even in the presence of external disturbances is illustrated. The proposed approach is based on the compensation of the dynamic coupling between the robotic arm and the unmanned aerial vehicle. Stability is analytically proved, and the effectiveness of the proposed control solution is shown with some simulations.